COOLFACADE: Architectural integration of solar cooling strategies in the building envelope - Prieto Hoces, Alejandro (A+BE | Architecture and the Built Environment, 2018)
The thesis ‘COOLFACADE – Architectural integration of solar cooling strategies in the building envelope’ aims to shed light on the possibilities and constraints for architectural integration of solar cooling systems in façades, in order to support the design of climate responsive architectural products for office buildings as self-sufficient alternatives to conventional air-conditioning systems. Increasing cooling needs in the built environment present an important and complex challenge for the design of sustainable buildings and cities. Even though the first course of action should always aim to reduce energy consumption through saving measures and passive design, this is often not enough to avoid mechanical equipment altogether, particularly in the case of office buildings in warm climate contexts. Solar cooling technologies have been increasingly explored, as an environmentally friendly alternative to harmful refrigerants used within vapour compression systems; while also being driven by solar, thus, renewable energy. The principles behind some of these technologies have been researched for over a century, reaching mature solutions and components, and being recognised as promising alternatives to common air-conditioning units. Nonetheless, building application remains mostly limited to demonstration projects and pilot experiences. Recently, façade integrated concepts have been explored, as a way to promote widespread application throughout the development of multifunctional building components. However, while these are regarded as relevant and promising standalone concepts, further research is still needed to assess the integration potential of diverse solar cooling technologies, and identify barriers to overcome, in order to promote the widespread application of solar cooling components in the built environment. The aim of this research project is to explore the possibilities and constraints for architectural integration of solar cooling strategies in façades, in order to support the design of climate responsive architectural products for office buildings, without compromising the thermal comfort of users. The underlying hypothesis then is that self-sufficient solar cooling integrated facades may be a promising alternative to conventional centralised air-conditioning systems widely used in office buildings in warm climates. Most research efforts on solar cooling currently deal with the optimisation of the systems in terms of their performance, testing new materials and simplifying their operation to increase reported efficiencies. However, there is a lack of knowledge on the requirements and current limits for widespread façade application. In order to achieve the research goal and comprehensively assess the façade integration potential of solar technologies and discuss current barriers, different aspects must be acknowledged. These distinct aspects are addressed through several research questions, which in turn define the different chapters of the dissertation. Introduction and conclusions aside, the research body is structured on three sequential parts, with 2-3 chapters each. The first part deals with the state-of-the-art in the field and the theoretical framework, laying the groundwork for the following sections. The second part explores different aspects required as input for façade integration; while the third part comprises the evaluation of solar cooling technologies in terms of current possibilities and constraints for the development of integrated façades, based on the inputs identified in the second part. Furthermore, all chapters were published or submitted for publication as scientific articles in peer review academic journals. The first part considers two chapters that lay the foundations for the research project, The first chapter after the introduction expands the background of the dissertation by identifying knowledge gaps and research trends while contributing to the generation of a reference database of research experiences, throughout a systematic literature review of cooling research in office buildings during the last 25 years. On the other hand, the following chapter delves specifically in the main themes addressed within the dissertation, proposing a framework for the understanding of solar cooling integrated façades. This considers the theoretical discussion of the concept of architectural façade integration; and the identification of the main working principles and technical components from most common solar cooling technologies, based on a state-of-the-art review. The second part explores different required inputs for façade integration. Design and construction requirements for façade integration are explored; while the response from façade design parameters to various climate conditions is assessed in parallel. The exploration of design and construction requirements is conducted through the identification of the main perceived problems for the façade integration of building services and solar technologies, by means of a survey addressed to façade professionals. On the other hand, a separate chapter explores the relation between climate conditions and cooling requirements in office buildings, evaluating the potential impact of several passive cooling strategies in various warm climates, as a first step before considering further technologies. This was conducted through the statistical analysis of reported research experiences, and dynamic energy simulations of a base scenario using specialised software. The third part of the dissertation consists of two chapters that incorporate previous outcomes for the evaluation of selected solar cooling technologies in terms of current possibilities and constraints for the development of integrated façades. The first of these chapters showcases a qualitative evaluation of the façade integration potential of several solar cooling technologies, based on a comprehensive review of key aspects of each technology and their prospects to overcome the identified barriers for façade integration. This is complemented by a feasibility assessment of integrated concepts in several climates, throughout numerical calculations based on climate data and building scenarios simulated with specialised software; showcased in the following and final chapter. The driving force of the research project is the intention to test the limits of solar cooling integration in façades, showcasing current possibilities while identifying technical constrains and barriers to overcome for the widespread application of integrated façade concepts. Although interesting prospects were identified in this dissertation, important technical constraints need to be solved to conceive a façade component fail-tested for application in buildings. Furthermore, several barriers related to the façade design and development process would need to be tackled in order to introduce architectural products such as these into the building market. The identification and discussion of these barriers, along with the definition of technology driven development paths and recommendations for the generation of distinct architectural products, are regarded as the main outcomes of this dissertation, serving as a compass to guide further explorations in the topic, under an overall environmentally conscious design approach.